Recent Advances in One-Dimensional Micro/Nanomotors: Fabrication, Propulsion and Application - Zheng, Yuhong; Zhao, He; Cai, Yuepeng; Jurado‑Sánchez, Beatriz; Dong, Renfeng (Nano-Micro Letters, 2022)
Due to their tiny size, autonomous motion and functionalize modifications, micro/nanomotors have shown great potential for environmental remediation, biomedicine and micro/nano-engineering. One-dimensional (1D) micro/nanomotors combine the characteristics of anisotropy and large aspect ratio of 1D materials with the advantages of functionalization and autonomous motion of micro/nanomotors for revolutionary applications. In this review, we discuss current research progress on 1D micro/nanomotors, including the fabrication methods, driving mechanisms, and recent advances in environmental remediation and biomedical applications, as well as discuss current challenges and possible solutions. With continuous attention and innovation, the advancement of 1D micro/nanomotors will pave the way for the continued development of the micro/nanomotor field. Highlights: 1 In-depth overview of the classification of one-dimensional (1D) micro/nanomotors and strategies for fabricating them are reviewed. 2 Driving mechanisms and progress of 1D micro/nanomotors for applications are summarized. 3 Challenges and future prospects of 1D micro/nanomotors are discussed.